AFFIRMATION OF WOMEN'S REPRESENTATIVENESS AND ELECTABILITY IN THE IMPLEMENTATION OF THE 2024 SIMULTANEOUS ELECTIONS IN SUMBAWA ISLAND, WEST NUSA TENGGARA - Puspitasari, Essy; Firmanto, Taufik; Hadijah (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
The purpose of this study is to try to find out the rationality of Affirmation of Women's Representation and Electability in the Implementation of Simultaneous Elections in 2024 on Sumbawa Island, West Nusa Tenggara, what are the policies and obstacles encountered. The method used in this study is a mixed method research method where several methods are combined in one research, such as normative methods with empirical methods. Results from this study shows that the quota for women of at least 30 began to be enforced in the 2004 election. However, up to the last legislative election, which was 22.1%. The hope of achieving a minimum quota of 30% female representation has not been met. The originality of this study shows that so far there has been no research on the Affirmation of Women's Representation and Electability in the Implementation of Simultaneous Elections in 2024 on Sumbawa Island, West Nusa Tenggara.